PENYULUHAN APLIKASI PENCATATAN NAFSIYAH SISWA BERBASIS ANDROID DI SMA BINA INSAN MANDIRI: PENYULUHAN APLIKASI PENCATATAN NAFSIYAH SISWA BERBASIS ANDROID DI SMA BINA INSAN MANDIRI - Candra Maulana, Wendy Asswan Cahyadi, Suhendra Anjar Dinata (Jurnal Teknorama (Informatika dan Teknologi El Rahma), 2025)
Education in the digital era requires technological innovation that can support the teaching and learning process and monitor students' emotional and psychological conditions effectively. Recording students' psychological conditions is very important to help guidance and counseling teachers and teaching staff in monitoring and providing appropriate interventions if psychological problems are found in students. SMA Bina Insan Mandiri, as an educational institution committed to developing student potential holistically, requires practical and efficient solutions in terms of recording and monitoring students' psychological conditions. Therefore, this Community Service activity aims to provide counseling and training on Android-based nafisiyah recording applications to teaching staff and guidance and counseling staff at SMA Bina Insan Mandiri